1999
DOI: 10.1111/j.1749-6632.1999.tb07962.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Cell Membrane Alteration: Evidence for Surfactant‐Mediated Sealinga

Abstract: Exposure to very intense ionizing irradiation produces acute tissue sequelae including inflammation, pain, and swelling that often results in tissue fibrosis and/or necrosis. Acute tissue necrosis occurs in hours when sufficiently rapid damage to membrane lipids and proteins leads to altered membrane structure, disrupting the vital electrochemical diffusion barrier necessary for cell survival. This damage mechanism is thought to underlie the interphase death of lethally irradiated postmitotic cells such as neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…2E). These latter observations were consistent with the prevailing idea that F-68 inserted into damaged plasma membrane and restored plasma membrane integrity through membrane sealing (Lee et al, 1993; Lee et al, 1992; Mina et al, 2009; Ng et al, 2008; Terry et al, 1999; Yasuda et al, 2005). …”
Section: Pluronic-mediated Cellular Rescue From Injury: State Of Tsupporting
confidence: 91%
“…2E). These latter observations were consistent with the prevailing idea that F-68 inserted into damaged plasma membrane and restored plasma membrane integrity through membrane sealing (Lee et al, 1993; Lee et al, 1992; Mina et al, 2009; Ng et al, 2008; Terry et al, 1999; Yasuda et al, 2005). …”
Section: Pluronic-mediated Cellular Rescue From Injury: State Of Tsupporting
confidence: 91%
“…Poloxamines are known to be capable of sealing cell membranes [18,38]. It has been shown that cell membrane sealing requires a decrease in surface tension and this is naturally provided by Ca 2+ -dependent exocytosis of new membrane near the site of disruption [39].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, P188 has been shown to protect against glutamate toxicity in the rat brain10 and protect embryonic hippocampal neurons against death due to neurotoxic‐ induced loss of membrane integrity11,12 and reduce the leakage of normally membrane impermeant calcein dye from high‐dose irradiated primary isolated skeletal muscle cells 13. Other surfactants, such as poloxamine 1107 (P1107), have been shown to reduce testicular ischemia‐reperfusion injury,14 hemoglobin leakage from erythrocytes after ionizing radiation,15,16 and propidium iodine uptake of lymphocytes after high‐dose ionizing irradiation 17. In all the aforementioned investigations, the observed phenomena were attributed to sealing of permeabilized cell membranes by the surfactants.…”
Section: Surfactant Sealing Of Cell Membranesmentioning
confidence: 99%